Fringe pattern analysis for optical metrology : theory, algorithms, and applications /: theory, algorithms, and applications. ([2014]) - Servín, Manuel; Quiroga, J. Antonio (Juan Antonio); Padilla, J. Moisés (José Moisés)
No abstract available